Optimisation de la puissance optimale : une nouvelle technique de commande MPPT pour une efficacité améliorée dans les systèmes photovoltaïques durables - BELACHI WAFA; BIRANE Mouhoub (Université Amar Thelidji- Laghouat FACULTE: DE TECHNOLOGIE DEPARTEMENT ELECTRONIQUE, 2025)
This thesis aims to improve the efficiency of photovoltaic systems using Maximum Power Point Tracking (MPPT) techniques to optimize energy extraction under various climatic conditions. It compares the Perturb and Observe algorithm with Fuzzy Logic Control, supported by a MATLAB/SIMULINK simulation to analyze system response. The methods were integrated with Boost converters and battery storage to achieve a more efficient and sustainable system, resulting in higher efficiency, reduced losses, and improved production reliability.
Option : Instrumentation